Antioxidant and antidiabetic potential of Myrothamnus flabellifolius found in Botswana. Issue 1 (31st December 2016) - Kwape, Tebogo E.; Majinda, Runner R.T.; Chaturvedi, Padmaja
Abstract: The total phenol content, antioxidant and antidiabetic activity of Myrothamnus flabellifolius (MF) were investigated. The study revealed 70% ethanol/water (EW70), 70% methanol/water (MW70) and methanol (Me) extracts to contain the highest phenol content, 350 mg GAE/g, 300 mg GAE/g and 250 mg GAE/g, respectively (GAE/g—Gallic Acid Equivalent per gram). MW70 exhibited the highest radical [diphenyl picryl hydrazine (DPPH) and 2, 2-Azobis-3-ethyl benzthiazoline-6-sulphonic acid (ABTS + )] scavenging power. About 70% ethanol/water exhibited the highest reducing power, hydrogen peroxide and nitric oxide scavenging activities. The results of antidiabetic activity showed EW70 to possess the highest α -amylase inhibitory effect. The α -glucosidase activity was inhibited by EW70, n-Butanol fraction and ethyl acetate fraction, respectively. The results of the study suggest MF as a beneficial natural medicine.